The New Multilateralism in South African Diplomacy
X, 222 p.
Keywords: The New Multilateralism in South African Diplomacy provides a detailed analysis of how post-apartheid South Africa has participated in multilateral diplomacy in a variety of sub-regional, regional and international settings during the last decade. The book will interest scholars interested in multilateralism and South African foreign policy.